Forced feeding of convicts: problems of theory and practice - Yu. V. Orel; R. R. Galán Vioque (Bulletin of Kharkiv National University of Internal Affairs)
The problematic issues of legislative consolidation and application of forced feeding to convicts who refuse to take food in institutions of execution of punishment are considered.